THE EFFECT OF WORK MOTIVATION, WORK ENVIRONMENT, AND COMPENSATION ON EMPLOYEE PERFORMANCE AT BANK BTN MEDAN BRANCH OFFICE - Pangabean, Sesylia Natali Br; Dirbawanto, Nana Dyki; Siregar, Onan Marakali (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study aimed to assess the impact of employee motivation, work environment, and remuneration on performance at the Bank BTN Medan Branch Office. This study employs quantitative methodologies and utilizes 40 employees as samples. The sampling is determined by saturation sampling. A questionnaire with a Likert scale is distributed directly to respondents to collect data. Instrument test of reliability and validity, classical assumption test, and hypothesis test utilizing multiple linear regression analysis and SPSS. The findings revealed that work motivation, work environment, and salary had a significant and positive impact on the performance of Bank BTN Medan Branch Office personnel, either partially or simultaneously. The effect obtained was on the value of 75.7%, means that work motivation, work environment, and compensation received have a significant influence on the performance of its employees, although it is necessary to increase certain aspects so that the increase will also improve and enhance the performance of the employees of the Bank BTN Medan Branch Office.